2004
DOI: 10.1260/147547204323022248
|View full text |Cite
|
Sign up to set email alerts
|

Airframe Noise Study of a Bombardier CRJ-700 Aircraft Model in the NASA Ames 7-by 10-Foot Wind Tunnel

Abstract: NOMENCLATURE d fs distance from noise source to receiver full scale d ss distance from noise source to receiver small scale f frequency, Hz fs full scale f45°flap deflection angle = 45 deg i t horizontal-stabilizer incidence angle, deg Lp sound pressure level, dB relative to 20 mPa M free-stream Mach number s25°slat deflection angle = 25 deg SF scale factor = 0.07 ss small scale a or alpha model angle of attack as measured on fuselage lower surface near wing, deg DdB change in noise level relative to baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…An integration method similar to that of Brooks et al 2 was used by Soderman et al 4 to determine the relative importance of different airframe noise sources in a closed wind tunnel. However, the reliability of the absolute and relative sound levels was not investigated, probably because single-microphone levels of the wall-mounted array were contaminated by flow noise.…”
Section: Introductionmentioning
confidence: 99%
“…An integration method similar to that of Brooks et al 2 was used by Soderman et al 4 to determine the relative importance of different airframe noise sources in a closed wind tunnel. However, the reliability of the absolute and relative sound levels was not investigated, probably because single-microphone levels of the wall-mounted array were contaminated by flow noise.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional beamforming technique together with the diagonal removal and the spectral background noise subtraction ( [45]) provides sufficient SNR to eliminate background noise and reverberations in the closed test section ( [46,47]). More details are given in [36,37].…”
Section: Beamforming Methodologiesmentioning
confidence: 99%
“…In terms of noise, it is apparent that local flow separations are a dominant source in the landing phase. For example, an experimental study conducted for the Bombardier CRJ-700 regional jet identified the most significant sources of noise in the landing configuration (5) . Of the ten most significant sources, five were directly attributable to the high-lift system, and it was noted that both increased incidence and device deflection resulted in increased noise.…”
Section: Study Of the Historical Development Of Other Disruptivementioning
confidence: 99%
“…In the high lift configuration and particularly with the undercarriage deployed, significant noise sources are introduced. Some of these have been found to be attributable to the interacting vortices and wakes caused by the flap ends and slots (5) . Given the current research, it is reasonable to presume that FC could be used to eliminate some of these problems by improving simply hinged flap performance and the control of unsteadiness in separating flows.…”
Section: Timeline For Single Aisle Replacement Aircraftmentioning
confidence: 99%